Doctors’ perspectives on adhering to advance care directives when making medical decisions for patients: an Australian interview study - Karen M Detering; Marcus Sellars; Linda Nolte; Scott Fraser; Nadia Moore; Tessa Low (BMJ Open)
Objective Advance care planning (ACP) assists people to identify their goals, values and treatment preferences for future care. Ideally, preferences are documented in an advance care directive (ACD) and used by doctors to guide medical decision-making should the patient subsequently lose their decision-making capacity. However, studies demonstrate that ACDs are not always adhered to by doctors in clinical practice. We aim to describe the attitudes and perspectives of doctors regarding ACD adherence and the utility of ACDs in clinical practice.Design Face-to-face semistructured interviews were conducted using three case-based vignettes to explore doctors’ decision-making and attitudes towards ACDs. Transcripts were analysed using a thematic analysis.Setting Doctors from a variety of medical specialties and with varying experience levels were recruited from a large tertiary hospital in Melbourne, Australia.Participants A total of 21 doctors were interviewed, 48% female (10/21). Most (19/21) reported having experience using ACDs.Results Four themes were identified: aligning with patient preferences (avoiding unwanted care, prioritising autonomy and anticipating family opposition), advocating best interests (defining futile care, relying on clinical judgement, rejecting unreasonable decisions and disregarding legal consequences), establishing validity (doubting rigour of the decision-making process, questioning patients’ ability to understand treatment decisions, distrusting outdated preferences and seeking confirmation) and translating written preferences into practice (contextualising patient preferences, applying subjective terminology and prioritising emergency medical treatment).Conclusions ACDs provide doctors with opportunities to align patient preferences with treatment and uphold patient autonomy. However, doctors experience decisional conflict when attempting to adhere to ACDs in practice, especially when they believe that adhering to the ACD is not in the patients’ best interests, or if they doubt the validity of the ACD. Future ACP programmes should consider approaches to improve the validity and applicability of ACDs. In addition, there is a need for ethical and legal education to support doctors’ knowledge and confidence in ACP and enacting ACDs.